1990
DOI: 10.1093/ajcn/51.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and hormonal evaluation of men at different risks for prostate cancer: plasma and fecal hormone-nutrient interrelationships

Abstract: Relationships between dietary nutrients and plasma and fecal estrone, estradiol-17 beta, testosterone, and plasma prolactin concentrations were studied in young Seventh-day Adventist men: 18 nonvegetarians (NVs), 20 lactoovovegetarians (LOVs), and 15 vegans (V). Blood samples and 3-d dietary records were obtained. Contemporaneously collected diet composites and stool samples were analyzed for fiber. Vs and LOVs consumed significantly more fiber than did the omnivores, whereas NVs and LOVs consumed more saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…Chan et al (1998) found that men who subsequently developed prostate cancer had 8% higher serum IGF-I concentrations than men who remained healthy, suggesting that the 9% difference we observed is large enough to significantly alter prostate cancer risk. SHBG was significantly higher in the vegans than in the meateaters, leading to a corresponding increase in T in order to maintain constant levels of FT, a pattern which has been found in previous smaller observational studies (Key et al, 1990;Pusateri et al, 1990). The differences in SHBG concentrations between dietary groups were reduced but not eliminated by adjusting for differences in BMI, suggesting that nutritional factors specific to a vegan diet may be important determinants of circulating SHBG levels, over and above their effect on BMI.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Chan et al (1998) found that men who subsequently developed prostate cancer had 8% higher serum IGF-I concentrations than men who remained healthy, suggesting that the 9% difference we observed is large enough to significantly alter prostate cancer risk. SHBG was significantly higher in the vegans than in the meateaters, leading to a corresponding increase in T in order to maintain constant levels of FT, a pattern which has been found in previous smaller observational studies (Key et al, 1990;Pusateri et al, 1990). The differences in SHBG concentrations between dietary groups were reduced but not eliminated by adjusting for differences in BMI, suggesting that nutritional factors specific to a vegan diet may be important determinants of circulating SHBG levels, over and above their effect on BMI.…”
Section: Discussionsupporting
confidence: 79%
“…The nutritional determinants of circulating hormone levels in men are poorly understood; some previous studies suggested that a vegetarian diet, low in saturated fat and high in dietary fibre, might reduce androgen levels, but the results have been inconsistent and based on small numbers (Deslypere and Vermeluen, 1984;Howie and Shultz, 1985;Bélanger et al, 1989;Key et al, 1990;Pusateri et al, 1990). We are not aware of any previous data on IGF-I concentrations in vegetarian and vegan men.…”
mentioning
confidence: 99%
“…Furthermore, the differences in diet of both populations could potentially have affected the fGCM concentration levels measured in this study. Differences in diet patterns have been shown to affect the composition and abundance of various gut bacteria in wildlife species (Pusateri et al 1990) and could have therefore an effect on the degree of hormone metabolism performed and subsequently an influence on the hormone metabolite concentration excreted (Gorbach and Goldin 1987;Morrow et al 2002). Although there are contradicting findings on the effect of diet on hormone metabolism and excretion (Dantzer et al 2011;Goymann 2012), the use of anthropogenic food sources could be an important factor when quantifying fGCM excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the relationships between diet and serum androgens and estrogens in men (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), but none of the studies have assessed the association of the hormones with dietary soy. Here we present a study of the cross-sectional relationships of soy product intake to serum androgens and estrogens in Japanese men.…”
Section: Introductionmentioning
confidence: 99%